DIGITAL GOVERNANCE AS A CONDITIONAL ANTI-FRAUD MECHANISM: THE INTERACTIVE EFFECTS OF ELECTRONIC PROCUREMENT, ELECTRONIC GOVERNMENT, AND BERAKHLAK ORGANIZATIONAL CULTURE - Safitri, Rika Henda; Susetyo, Didik; Saftiana, Yulia; Yusrianti, Hasni (LPPM Universitas Jambi, 2026)
Fraud in public procurement remains a persistent governance problem despite the widespread implementation of digital systems in the public sector. Although prior studies confirm that e-procurement and e-government enhance transparency, empirical evidence integrating digital governance and organizational culture in explaining fraud detection effectiveness remains limited, particularly at the ministerial level in developing countries. This study aims to examine the impact of e-procurement and e-government on fraud detection and to analyze the moderating role of BerAKHLAK organizational culture within the Indonesian Ministry of Immigration and Corrections. This research employs a quantitative approach using survey data collected from 320 procurement and budget officials across 33 provinces in 2024-2025. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to evaluate both direct and moderating effects. The results indicate that e-procurement (β=0,451; p<0,001) and e-government (β=0,357; p<0,001) have positive and significant effects on fraud detection. Furthermore, BerAKHLAK organizational culture significantly strengthens the influence of both e-procurement (β = 0,307, p<0,001) and e-government (β = 0,315, p < 0,001). The structural model explains 63,6% of the variance in fraud detection, demonstrating substantial explanatory power. This study offers novelty by developing an integrated moderated model that positions organizational culture as a contextual enhancer of digital fraud control mechanisms. The findings extend Agency Theory, the Theory of Planned Behavior, and fraud hexagon theory within a digital governance context. Practically, the results highlight that technological sophistication alone is insufficient; effective fraud detection requires the simultaneous strengthening of ethical organizational values to ensure sustainable and accountable public governance.